Confinement Effects in Dynamics of Ionic Liquids with Polymer‐Grafted Nanoparticles. Issue 18 (14th July 2022) - Liu, Siqi; Li, Ruhao; Tyagi, Madhusudan; Akcora, Pinar
Abstract: Ionic liquid mixed with poly(methyl methacrylate)‐grafted Fe3 O4 nanoparticle aggregates at low particle concentrations was found to exhibit different dynamics and ionic conductivity than that of pure ionic liquid in our previous studies. In this work, we report on the quasi‐elastic neutron scattering results of ionic liquid containing polymer‐grafted Fe3 O4 nanoparticles at higher particle concentrations. The diffusivity of imidazolium (HMIM + ) cations of 1‐hexyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide (HMIM‐TFSI) in the presence of poly(methyl methacrylate)‐grafted Fe3 O4 nanoparticles is discussed through the confinement. Analysis of the elastic incoherent structure factor revealed that the confinement radius decreased with the addition of grafted particles in HMIM‐TFSI/solvent mixture. We propose the confinement that is induced by the high concentration of grafted particles shrinks the HMIM‐TFSI restricted volume. We further conjecture that this enhanced diffusivity occurs as a result of the local ordering of cations within aggregates of poly(methyl methacrylate)‐grafted Fe3 O4 nanoparticles. Abstract : Grafted polymers on nanoparticles in 1‐hexyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide (HMIM‐TFSI) enhances the imidazolium cation (HMIM + ) diffusion as measured in quasi‐elastic neutron scattering spectrometer. This effect explained by the solvation of ionic liquid ions with the help of PMMA chains leads to the shrinkage of the cation confinement radius as grafted particle concentration increases.